A sustainable approach for efficient conversion of lignin into biodiesel accompanied by biological pretreatment of corn straw. (1st November 2019) - Zhang, Kai; Xu, Rong; Abomohra, Abd El-Fatah; Xie, Shangxian; Yu, Zhengsheng; Guo, Qian; Liu, Pu; Peng, Liang; Li, Xiangkai
Graphical abstract: Highlights: Mycobacterium smegmatis LZ-K2 prefer to degrade lignin rather than cellulose. The Fenton chemistry model, assists in degradation of lignin, exist in the strain LZ-K2. The strain LZ-K2 could effectively convert lignin in corn straw to lipid. Abstract: Lignin is the second-most abundant biopolymer on the Earth and it is hard to valorize without pretreatment due to its inherent heterogeneity and recalcitrance. Nowadays, it is necessary to develop effective innovative methods for lignin degradation and efficient utilization. In the present study, the lignolytic bacterium Mycobacterium smegmatis LZ-K2 was isolated from rotten wood. The isolate showed high lipid production and high efficiency of lignin degradation. The lipid production of LZ-K2 grown in corn straw medium with alkali pretreatment, acid pretreatment, and without chemical pretreatment were 0.083 g/L, 0.069 g/L, and 0.072 g/L, respectively. Fatty acids (C14-C24), especially palmitic acid (C16:0; 38.9%), were also accumulated in the untreated corn straw cultures. Results confirmed that the enzyme system and Fenton reaction are the major pathways for lignin depolymerization. In addition, the presence of a critical lignin-degrading enzymes, other than cellulase and hemicellulase, was revealed by the genome analysis. Moreover, the proteome of LZ-K2 showed enzymes, mainly glucose-methanol-choline (GMC) oxidoreductases, which are involved in the Fenton reaction and β-ketoadipate pathway. Unique enzymes of oleaginous microorganisms, such as acetyl CoA carboxylase, were also identified in LZ-K2. In conclusion, the present work provides a sustainable approach for efficient conversion of lignin into biodiesel with simultaneous biological pretreatment of lignocelluloses.